Image-based indexing and retrieval of trademark logo - Wang, Yan. (2008)
In this thesis, an image database application which is designed to store and index trademark information is discussed. The system is proposed to support the trademark registry. The specially designed retrieval prototype offers an effective and efficient retrieval for conflicting trademarks to a query image.